Legal Guarantees for Correctional Inmates under the 2005 Constitution of the Republic of Iraq - Jabbar Abbas Al-Shawi, Assist. Lect. Rana (Basra studies journal, 2026)
This research aims to shed light on the legal guarantees afforded to correctional inmates under Iraqi law. These individuals are deprived of their liberty as part of criminal penalty enforcement; however, this does not imply the loss of their humanity or fundamental rights. The Inmates and Detainees Reform Law No. 14 of 2018 guarantees a range of rights and protections for such inmates, including the right to human dignity, healthcare, education, freedom of belief, a fair trial, and protection from torture and ill-treatment. The study examines the shortcomings in the practical implementation of these guarantees, despite their clear articulation in the legal texts. Iraqi correctional institutions face various legislative, administrative, and financial challenges that impede the effective enforcement of these rights.